Long-term efficacy and safety of canagliflozin monotherapy in patients with type 2 diabetes inadequately controlled with diet and exercise: findings from the 52-week CANTATA-M study. (February 2014) - Stenlöf, Kaj; Cefalu, William T.; Kim, Kyoung-Ah; Jodar, Esteban; Alba, Maria; Edwards, Robert; Tong, Cindy; Canovatchel, William; Meininger, Gary
Abstract Objective: Canagliflozin is a sodium glucose co-transporter 2 inhibitor developed for treatment of type 2 diabetes mellitus (T2DM). The long-term efficacy and safety of canagliflozin monotherapy were evaluated over 52 weeks in patients with T2DM inadequately controlled with diet and exercise. Research design and methods: This randomized, double-blind, Phase 3 study included a placebo-controlled, 26-week core period (canagliflozin 100 or 300 mg vs placebo) and an active-controlled, 26-week extension (blinded switch of placebo-treated patients to sitagliptin 100 mg [placebo/sitagliptin]). Clinical trial registration: ClinicalTrials.gov, NCT01081834. Main outcome measures: Efficacy endpoints assessed at 52 weeks included changes in hemoglobin A1c (HbA1c), fasting plasma glucose (FPG), and systolic blood pressure (BP); and percentage changes in body weight and fasting plasma lipids. Adverse events (AEs) were recorded throughout the study. Efficacy data are reported for canagliflozin 100 and 300 mg (placebo/sitagliptin group was used to maintain the double-blind and to serve as a control group for safety purposes; not as an efficacy comparator); safety data are reported for canagliflozin 100 and 300 mg and placebo/sitagliptin. Results: Efficacy analyses included 451 patients who were randomized and dosed, entered the extension, and did not receive rescue therapy during the core period. Safety analyses included 584 patients who were randomized and dosed. At Week 52, canagliflozin 100 and 300 mg provided dose-related decreases from baseline in HbA1c of −0.81% and −1.11%. Canagliflozin 100 and 300 mg decreased FPG (−1.5 and −2.2 mmol/L [−27.4 and −39.1 mg/dL]), body weight (−3.3% and −4.4%), and systolic BP (−1.4 and −3.9 mmHg); decreased triglycerides and increased HDL-C and LDL-C were also seen. Over 52 weeks, overall AE rates were 67.2%, 66.0%, and 64.1% with canagliflozin 100 and 300 mg and placebo/sitagliptin; rates of serious AEs and AE-related discontinuations were low across groups. Compared with placebo/sitagliptin, canagliflozin was associated with higher rates of genital mycotic infections and AEs related to osmotic diuresis; these led to few discontinuations. Rates of volume depletion AEs and documented hypoglycemia were low across groups. Conclusions: Canagliflozin monotherapy provided sustained improvement in glycemic control and body weight reduction, and was generally well tolerated in patients with T2DM over 52 weeks.